“Five F” on Prevention of Disease Transmission Among Mothers of Under Five Children: Life Sciences-Nursing - Mahalakshmi, B.; Kandarpkumar, Patel Arpit; Subramanian, N. Siva; Prakash, D. (International Journal of Life Science and Pharma Research, 2022)
The pathogenic microorganisms that cause infection, such as "bacteria, viruses, parasites, or fungus," can spread from one person to another either directly or indirectly. Infection spreads through direct contact from person to person, contact of body fluids, any secretions or even the fomite used by the infected person. The oral fecal route can be summarized into five f: - finger, food, fluid, feces, and flies. The Aim and objective of the study were to assess the knowledge regarding Five 'F' diseases transmission among mothers of under-five children to evaluate the effectiveness of sensitization program on knowledge regarding Five 'F' of disease transmission among mothers of under-five children and to find out the association between post-test knowledge scores and selected demographic variables among mothers of under-five children. "Pre-experimental research design" was used for the study and data were collected from 60 under five mothers by "nonprobability convenient sampling method", through a structured knowledge questionnaire. Data were analyzed using "descriptive and inferential statistics" such as standard deviation, mean, and chi-square tests. The mean post-test knowledge score (22.62±3.37) was higher than the mean pretest knowledge score (13.3±3.30). The calculated value (15.28) was more significant than the table value (1.67) at 0.05 level of significance, that shows the sensitization program was effective in increasing the knowledge regarding the prevention of "Five f" (finger, food, fluid, feces, flies) diseases transmission among mothers of under-five children.